Montgomery in the Good War : Portrait of a Southern City, 1939-1946. - Newton, Wesley Phillips (University of Alabama Press, 2000)
Montgomery in the Good War is a richly textured account of a southern city and its people during World War II. Using newspaper accounts, interviews, letters, journals, and his own memory of the time, Wesley Newton reconstructs wartime-era Montgomery, Alabama--a sleepy southern capital that was transformed irreversibly during World War II. The war affected every segment of Montgomery society: black and white, rich and poor, male and female, those who fought in Europe and the Pacific and those who stayed on the home front. Newton follows Montgomerians chronologically through the war from P.